PLANNING DESIGN OF FENCE OF AL-MUNAWARAH MUSHOLLA, KAJHU, ACEH BESAR DISTRICT - Hidayat, Rifki; Azka, Cut Nawalul; Hafisah, Cut Nanda; Bahagia, Nurul (Universitas Muhammadiyah Aceh, 2021)
Al-Munawarah Mosque is one of the prayer rooms located in Kajhu Indah, Aceh Besar. Which one to functions as a place of worship, but also has a role as a means of community interaction, such as playgroup, Al Qur'an of Education and sport. The purpose is to give a specially design for mosque between administrators and the community about the importance of discussion and consultation on design in planning for fence renovations in their environment. The expected output from the implementation of this program is to produce a good decorative design element on the fence, so that the fence can be realized as magnificent and beautiful as possible. Almost around the fence on the outer side of the mosque, it is no longer feasible so renovation is needed. To achieve this, a good design concept is used and a method of assisting design consulting services so that the objectives of this program can be appropriate as needed together. The final result obtained is a design consulting service regarding the design concept and the details on the renovation of this fence can guarantee success in the implementation of this renovation.Keywords: Planning, Construction, Concept.Al-Munawarah Mosque is one of the prayer rooms located in Kajhu Indah, Aceh Besar. Which one to functions as a place of worship, but also has a role as a means of community interaction, such as playgroup, Al Qur'an of Education and sport. The purpose is to give a specially design for mosque between administrators and the community about the importance of discussion and consultation on design in planning for fence renovations in their environment. The expected output from the implementation of this program is to produce a good decorative design element on the fence, so that the fence can be realized as magnificent and beautiful as possible. Almost around the fence on the outer side of the mosque, it is no longer feasible so renovation is needed. To achieve this, a good design concept is used and a method of assisting design consulting services so that the objectives of this program can be appropriate as needed together. The final result obtained is a design consulting service regarding the design concept and the details on the renovation of this fence can guarantee success in the implementation of this renovation.Keywords: Planning, Construction, Concept.